2018
DOI: 10.1016/j.scr.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and high yield isolation of myoblasts from skeletal muscle

Abstract: Skeletal muscle (SkM) regeneration relies on the activity of myogenic progenitors that reside beneath the basal lamina of myofibers. Here, we describe a protocol for the isolation of the SkM progenitors from young and old mice by exploiting their outgrowth potential from SkM explants on matrigel coated dishes in the presence of high serum, chicken embryo extract and basic fibroblast growth factor. Compared to other protocols, this method yields a higher number of myoblasts (10–20 million) by enabling the outgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 36 publications
0
65
0
Order By: Relevance
“…Moreover, further myosatellite markers were examined in cells obtained from the 1-day-old chicks: MyoD and myogenin, as well as known myogenic regulatory factors and desmin, which is a generally accepted marker of satellite cells after three days in culture [19,26,27]. Desmin was detected in 100% of the isolated cells, while the levels of MyoD, myogenin and Pax7 reflected previously reported in vivo levels of cells expressing the three markers [28].…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, further myosatellite markers were examined in cells obtained from the 1-day-old chicks: MyoD and myogenin, as well as known myogenic regulatory factors and desmin, which is a generally accepted marker of satellite cells after three days in culture [19,26,27]. Desmin was detected in 100% of the isolated cells, while the levels of MyoD, myogenin and Pax7 reflected previously reported in vivo levels of cells expressing the three markers [28].…”
Section: Discussionmentioning
confidence: 60%
“…It has also been shown that 95% of the preplated rat muscle cells from the hind limb and back were positive for desmin and MyoD (Sheehan, Tatsumi, Temm‐Grove, & Allen, 2000). The purity of mouse myoblasts was increased up to 98% through preplating based on the expression of myogenic markers such as integrin α7, MyoD, and desmin (Shahini et al., 2018). Moreover, Qu‐Petersen et al.…”
Section: Muscle Stem Cell Isolation From Tissuesmentioning
confidence: 99%
“…The stemness of the cells significantly increased in a dose‐dependent manner under these conditions. Furthermore, high serum‐containing media with 20% FBS and 10% HS exclusively promote mouse muscle stem cell proliferation compared with that of nonmyogenic cells, especially fibroblasts (Shahini et al., 2018; Wang et al., 2014). Currently, due to the donor animal‐based wide variations in their composition, serum replacements, such as knockout serum replacement (KSR), and N2/B27 supplements are used to obtain consistent experimental results.…”
Section: In Vitro Culture Of Muscle Stem Cellsmentioning
confidence: 99%
“…In order to generate implantable neuromuscular constructs with anatomical relevance, we propose to stretch-grow engineered motor neuron aggregates on a bed of pre-differentiated myofibers grown on a suitable substrate 166 . Motor neurons can be harvested from rodent spinal cords 182 or obtained from differentiated human PSCs 183 using published protocols, while skeletal muscle cells can be sourced from cell lines, rodents 184 , or human PSCs 185 . This concept would entail culturing the skeletal muscle cells on a scaffold for 4-7 days in differentiation media to allow for the formation of myofibers prior to introduction and mechanical stretch of motor neurons in mechanobioreactors.…”
Section: Pre-innervated Skeletal Musclementioning
confidence: 99%